PENGARUH PENERAPAN ETIKA BISNIS ISLAM DAN KUALITAS MANAJEMEN PELAYANAN TERHADAP TINGKAT KEPUASAN KONSUMEN SOFYAN HOTEL BETAWI SYARIAH - Dewi Pitriani; Ibdalsyah Ibdalsyah; Hilman Hakiem (Univ Ibn Khaldun Bogor, 2020)
This study aims to determine the effect of the application of Islamic business ethics and the quality of service management at Sofyan Hotel Betawi Syariah Menteng on the level of consumer satisfaction. This type of research uses a quantitative approach. The population is visitors to the Sofyan Hotel Betawi Syariah Menteng, with a sample of 30 respondents. The sampling technique in this study is an accidental sampling. This study used a multiple linear regression analysis methods. The results of the study conducted obtained the coefficient of determination test results of 0,776. This shows that the percentage influence of Islamic business ethics and service management variables on the level of customer satisfaction is 77,6%. While the remaining 22,4% is influenced by other factors that are not included in this study. Simultaneously it can be stated that there is an influence between Islamic business ethics and service management together on the level of customer satisfaction at Sofyan Hotel Betawi Syariah Menteng, with a significance value of 0,000, it can be interpreted that the significance value is < 0,05. So it means that there is a positive influence between Islamic business ethics and service management on the level of customer satisfaction at Sofyan Hotel Betawi Syariah Menteng. Partially Islamic business ethics has no influence on the level of customer satisfaction Sofyan Hotel Betawi Syariah Menteng with a significance value of 0,316 > 0,05. While partially service management has an influence on the level of consumer satisfaction Sofyan Hotel Betawi Syariah Menteng with a significance value generated 0,000 < 0,05.